Cep55 overexpression causes male‐specific sterility in mice by suppressing Foxo1 nuclear retention through sustained activation of PI3K/Akt signaling. Issue 9 (17th April 2018) - Sinha, Debottam; Kalimutho, Murugan; Bowles, Josephine; Chan, Ai-Leen; Merriner, D. Jo; Bain, Amanda L.; Simmons, Jacinta L.; Freire, Raimundo; Lopez, J. Alejandro; Hobbs, Robin M.; O'Bryan, Moira K.; Khanna, Kum Kum
ABSTRACT: Spermatogenesis is a dynamic process involving self‐renewal and differentiation of spermatogonial stem cells, meiosis, and ultimately, the differentiation of haploid spermatids into sperm. Centrosomal protein 55 kDa (CEP55) is necessary for somatic cell abscission during cytokinesis. It facilitates equal segregation of cytoplasmic contents between daughter cells by recruiting endosomal sorting complex required for transport machinery (ESCRT) at the midbody. In germ cells, CEP55, in partnership with testes expressed‐14 (TEX14) protein, has also been shown to be an integral component of intercellular bridge before meiosis. Various in vitro studies have demonstrated a role for CEP55 in multiple cancers and other diseases. However, its oncogenic potential in vivo remains elusive. To investigate, we generated ubiquitously overexpressing Cep55 transgenic (Cep55 Tg / Tg )mice aiming to characterize its oncogenic role in cancer. Unexpectedly, we found that Cep55 Tg/Tg male mice were sterile and had severe and progressive defects in spermatogenesis related to spermatogenic arrest and lack of spermatids in the testes. In this study, we characterized this male‐specific phenotype and showed that excessively high levels of Cep55 results in hyperactivation of PI3K/protein kinase B (Akt) signaling in testis. In line with this finding, we observed increased phosphorylation of forkhead box protein O1 (FoxO1), and suppression of its nuclear retention, along with the relative enrichment of promyelocytic leukemia zinc finger (PLZF)—positive cells. Independently, we observed that Cep55 amplification favored upregulation of ret ( Ret ) proto‐oncogene and glial‐derived neurotrophic factor family receptor a‐1 ( Gfra1 ). Consistent with these data, we observed selective down‐regulation of genes associated with germ cell differentiation in Cep55‐overexpressing testes at postnatal day 10, including early growth response‐4 ( Egr4) and spermatogenesis and oogenesis specific basic helix‐loop‐helix‐1 ( Sohlh1 ). Thus, Cep55 amplification leads to a shift toward the initial maintenance of undifferentiated spermatogonia and ultimately results in progressive germ cell loss. Collectively, our findings demonstrate that Cep55 overexpression causes change in germ cell proportions and manifests as a Sertoli cell only tubule phenotype, similar to that seen in many azoospermic men.—Sinha, D., Kalimutho, M., Bowles, J., Chan, A.‐L., Merriner, D. J., Bain, A. L., Simmons, J. L., Freire, R., Lopez, J. A., Hobbs, R. M., O'Bryan, M. K., Khanna, K. K. Cep55 overexpression causes male‐specific sterility in mice by suppressing Foxo1 nuclear retention through sustained activation of PI3K/Akt signaling. FASEB J. 32, 4984–4999 (2018). www.fasebj.org